POPULATION STRUCTURE ANALYSIS OF MONKEYS IN SELECTED PROTECTED AND NON-PROTECTED AREAS OF PENINSULAR MALAYSIA - K. Karim; S. Anuar. M. S; Dauda T. O; H. Nidaullah (Journal of Animal and Plant Sciences, 2014)
Population of monkeys in Peninsular Malaysia has been inconsistent with regards to their numbers. At a certain times they deemed pest because of their large numbers, like Macaca fascicularis, a listed protected animal as per local Government jurisdiction. Here we evaluated population status along with recruitments rate, considering three species i.e. Long-tailed Macaques, Dusky-Leaf-Monkeys and Pig-tailed Macaques at seven randomly selected areas in Peninsular Malaysia. For analysis, Generalized Linear Model and Probability Density Function (pdf) analyses were conducted. As a result we perceived Kolmogorov values 0.153-0.479 and Anderson statistics 33.258-103.45. The geometric pdf ( prescribed P = 0.05114) which precisely coincides with the population distribution of the mentioned species. Further, it has been assumed that the smaller number of monkeys posses higher probability as compared with higher numbers in specified colony and vice versa. The results suggested that Bukit Selambau possessed highest parametric frequencies for some of the population indices except the adult male exhibited highest frequencies in Botanical gardens (x̅=2.917). Overall, species of Long-tailed Macaques was found predominantly (x̅=20.688) among the selected areas. Further, we established the colony size as 1- 17 individuals per group. Generally, the likelihood rate of recruitment index was 0.099 for the three species.
Keywords: Rate of recruitment; group size; seasonal effect; geometric pdf; adducible; Duncan Multiple range Test